PENGONTROLAN KEAMANAN SISTEM KOMPUTER CLIENT DARI SERANGAN HACKER DAN VIRUS KOMPUTER SECARA JARAK JAUH (REMOTE SERVER) DENGAN MENGGUNAKAN SSH - Jamaluddin Jamaluddin; El Rahmat Jaya Hulu; Rimbun Siringoringo (Universitas Methodist Indonesia, 2023)
Computer system security is very important to be considered by computer users to protect their computers from attacks such as hackers and computer viruses that can take data and damage the user's computer system. Hacker is a person or party who has the skill in breaking through and sneaking to access a computer without the user's permission and can take data and even damage the system on the user's computer. And a Computer Virus is a computer program that copies and inserts copies into the program and can damage the computer system. So that by using SSH (Secure Shell) can control and check computer security from hacker attacks and computer viruses without having to come to the location where there is a client computer or done remotely (Remote Server).